Virological Surveillance of Influenza Viruses during the 2008–09, 2009–10 and 2010–11 Seasons in Tunisia - El Moussi, Awatef (Public Library of Science, 2013)
BACKGROUND: The data contribute to a better understanding of the circulation of influenza viruses especially in North-Africa. OBJECTIVE: The objective of this surveillance was to detect severe influenza cases, identify their epidemiological and virological characteristics and assess their impact on the healthcare system. METHOD: We describe in this report the findings of laboratory-based surveillance of human cases of influenza virus and other respiratory viruses' infection during three seasons in Tunisia. RESULTS: The 2008–09 winter influenza season is underway in Tunisia, with co-circulation of influenza A/H3N2 (56.25%), influenza A(H1N1) (32.5%), and a few sporadic influenza B viruses (11.25%). In 2010–11 season the circulating strains are predominantly the 2009 pandemic influenza A(H1N1)pdm09 (70%) and influenza B viruses (22%). And sporadic viruses were sub-typed as A/H3N2 and unsubtyped influenza A, 5% and 3%, respectively. Unlike other countries, highest prevalence of influenza B virus Yamagata-like lineage has been reported in Tunisia (76%) localised into the clade B/Bangladesh/3333/2007. In the pandemic year, influenza A(H1N1)pdm09 predominated over other influenza viruses (95%). Amino acid changes D222G and D222E were detected in the HA gene of A(H1N1)pdm09 virus in two severe cases, one fatal case and one mild case out of 50 influenza A(H1N1)pdm09 viruses studied. The most frequently reported respiratory virus other than influenza in three seasons was RSV (45.29%). CONCLUSION: This article summarises the surveillance and epidemiology of influenza viruses and other respiratory viruses, showing how rapid improvements in influenza surveillance were feasible by connecting the existing structure in the health care system for patient records to electronic surveillance system for reporting ILI cases.